The effect of conspecific density, herbivory, and bamboo on seedling dynamics of a dominant oak in a Neotropical highland forest - Calderón Sanou, Irene (2019)
Conspecific negative density dependence (CNDD) is one of the main mechanisms influencing diversity maintenance in tropical forests. Tropical highland forests, in contrast to most lowland forests, are commonly dominated by a few tree species, and testing the importance of density dependence effects on seedling establishment of dominant trees may provide insights on the mechanisms regulating population dynamics and forest composition of tropical highlands. We tested the effect of CNDD regulation on seedling survival and recruitment of Quercus costaricensis, a monodominant oak in the Talamanca highland forests of Costa Rica. We used Ripley's K and generalized linear mixed models to test the effects of conspecific density, distance to the nearest adult, density of Chusquea bamboo shoots, and herbivory on the annual survival probability of 3579 seedlings between 2014 and 2017. We did not find a significant effect of CNDD on seedling survival. However, bamboo density and herbivory both significantly decreased oak seedling survival. All seedlings had signs of herbivory and predator satiation may explain the lack of density dependent regulation in seedlings of this species. We argue that the lack of intraspecific density regulation at the seedling stage may contribute to explain the dominance of Q. costaricensis in the highland forests of Costa Rica. Local seedling dynamics of this endemic oak are instead regulated by herbivory and the density of Chusquea.